Does SDGs Goal 8 Encompass in Stakeholders’ Roadmap of Indonesia’s Sharia Banking Journey: A preliminary exploration - Suprianto, Suprianto; Luthfi Zuhdi, Muhammad; Huda, Nurul; S, Basir (Dinasti International Journal of Economics, Finance & Accounting, 2024)
This study's objective is to present an interlinkage framework and analytical options through relevant reports and scientific publications of the roadmap that have been developed by institution as a stakeholder. It assesses the interlinkages between stakeholders’ roadmap and the comprehensive interactions among supported sector mentioned in these studies provides a key perspective for assessing the accomplishment of Sustainable Development Goals (SDGs) goal 8 objectives and its implementation. Using qualitative research approach that focused on understanding the nature of approaches or strategies that are interrelated between stakeholders’ roadmap that had the largest number of interlinkages and stimulate dialogue on the importance of aligning a broad exposure of stakeholders in achieving Decent Work and Economic Growth or SDGs goal 8 in Indonesia. A connection between approaches or strategies in each roadmap that linked with SDGs goal 8 through the same strategy represented in the graph using KUMU representing a direct relationship between a node and other node in the network. Overall, the result indicates that support to attain SDGs goal 8 were encompassing in various approaches or strategies in stakeholders’ roadmap.